Response rate in phone surveys: Experiments to test the effect of pre-visits and financial incentives - Neupane, Sumanta; Nguyen, Phuong Hong; Avula, Rasmi; Shapleigh, Sara; Heidkamp, Rebecca A. (International Food Policy Research Institute, 2022)
Household surveys play an important role in collecting cross-sectional information across time among population subgroups including demographics, health and nutrition risk factors and coverage of inteventions. During COVID-19 related lockdowns, phone surveys became a popular modality to collect such information in a safe and cost-effective manner. Compared to surveys using in-person interviews, phone-based surveys have limitations of non-representativeness and non-response errors which can result in biased estimates. There are, however, ways to mitigate some of these challenges.